2016
DOI: 10.1007/s10508-016-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Financial Risk Typologies Among Women Who Engage in Sex Work in Mongolia: A Latent Class Analysis

Abstract: Women engaged in sex work bear a disproportionate burden of HIV infection worldwide, particularly in low to middle income countries. Stakeholders interested in promoting prevention and treatment programs are challenged to efficiently and effectively target heterogeneous groups of women. This problem is particularly difficult because it is nearly impossible to know how those groups are composed a priori. Although grouping based on individual variables (e.g., age or place of solicitation) can describe a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Sixty-eight papers reporting on 56 unique studies with 24,940 participants meeting the inclusion criteria (Fig 1). Eight of these studies did not provide prevalence data on mental health [23][24][25][26][27][28][29][30][31]; authors of these studies were contacted twice for further information, and 2 authors responded, providing prevalence data [23,27]. In total, 86 prevalence estimates from 48 studies were available (depression n = 37; anxiety n = 7; PTSD n = 8; suicide attempt n = 8; suicide ideation n = 17; psychological distress n = 7; mood disorders n = 2) ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sixty-eight papers reporting on 56 unique studies with 24,940 participants meeting the inclusion criteria (Fig 1). Eight of these studies did not provide prevalence data on mental health [23][24][25][26][27][28][29][30][31]; authors of these studies were contacted twice for further information, and 2 authors responded, providing prevalence data [23,27]. In total, 86 prevalence estimates from 48 studies were available (depression n = 37; anxiety n = 7; PTSD n = 8; suicide attempt n = 8; suicide ideation n = 17; psychological distress n = 7; mood disorders n = 2) ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Social environment of sex work is widely considered risky to sexually and blood-transmitted diseases, as confirmed by numerous studies [1,3,21,22,23,29,30]. However, it proved to be receptive for many other illnesses as well, whose syndemic character has been insufficiently addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Wuttke et al analyzed the role of warehouse receipt pledge in accelerating the production and operation of agricultural products, discussed and studied the specific implementation process of the financing mode, and proposed the measures of risk prevention [16]. In 2016, Yan et al tried to analyze the risk of inventory management in the inventory pledge financing mode, and obtained the optimal goal of inventory with the expected utility to reduce the risk [17]. In 2017, Bustos et al demonstrated the degree to which the determination of interest rate and loan amount during the development of supply chain finance business influenced the risk through quantitative research, and proposed a conceptual model of supply chain finance risk analysis [18].…”
Section: Literature Reviewmentioning
confidence: 99%